Alan Greaves. The land of Ionia: society and economy in the Archaic period - Koparal, Elif (Journal of Greek Archaeology, 2016)
Ionia has been a key region in the political history of the ancient Greeks throughout the Archaic period. Although geographically it was peripheral to mainland Greece, located across the Aegean, it has been the epicenter of most events that have shaped ancient Greek culture. The region, more specifically the central part of the Western Anatolian coast and the islands of Chios and Samos, has been one of the focal points of Classical Archaeology practice since the 19th century. However, since then most of the effort has been confined to the excavation of temples and large town centers as well as the reconstruction of monumental buildings. In other words, Ionian archaeology mostly just fleshed out the past as offered by the literary sources.